Biochemical composition of dwarf mandarin cv. ‘Miagava-Vase’ in the humid subtropics of Russia - Kunina, V.; Soytong, K.; Song, J. J.; Belous, O. (My University, 2023)
The influence of growth regulators and biochemical composition of dwarf mandarin fruits was investigsated. It is shown that heavier fruits (44.8-48.2 g at 41.3 g in the control) are formed during treatment with siliplant, nanoelicitor and zerbra agro due to the formation of a thicker peel (20.1-20.9%), which is associated with the protective mechanism of these drugs which thicker peel is a mechanical protection against pathogens and phytoparasites. Siliplatin treatments provided a higher juice output about 54.5% compared to other growth regulators. Treatments with obstactin and silver agro significantly increased the fructose content in fruits (17.53-16.98 g / kg). The nanoelicitor variant has significantly higher sugar content (107.49 g /kg) due to the content is increased (73.12 g/kg). The use of growth regulators leaded to decrease in ascorbic acid (AA) to 30.61 mg / 100 g, which was shown to be an undesirable factor. The most significantly decreased in ascorbic acid (LSD = 8.27) was noted in variants with obstactin and siliplant treatments. Taking into account, the influence of growth regulators on plant resistance are increased AA synthesis under stress and decreased in ascorbic acid is associated with an improvement in the functional state of tangerine under the influence of non-root treatments. With the introduction of growth regulators, there was significantly increased in the amount of polyphenols (up to 9.33 mg /g at 7.72 mg /g in the control), especially on variants with treatments with obstactin (7.53 mg /g), siliplant (7.39 mg /g) and zerebra agro (7.33 mg/g). Treatments with growth regulators leaded to a significant increase in the Rutin in mandarin fruits (from 7.39 to 7.58 mg /g). The highest values of vitamin P were noted in the variant with obstactin and nanoelicitor treatment (7.53-7.58 mg/g at 6.68 mg/g). Nanoelicitor treatments accelerated fruit ripening, which represented to consumer value and economic benefits of growing crops for the resort town/area.
Keywords: Fruits; Growth regulators; Mandarin; Phenolic components; Quality; Vitamins